High Prevalence of GES-5 Variant and Co-Expression of VIM-2 and GES-45 among Clinical Pseudomonas aeruginosa Strains in Tunisia - Meha Fethi; Beatriz Rojo-Bezares; Ameni Arfaoui; Raoudha Dziri; Gabriela Chichón; Farouk Barguellil; María López; Mohamed Selim El Asli; Paula Toledano; Hadda-Imen Ouzari; Yolanda Sáenz; Naouel Klibi (MDPI AG, 2023)
Carbapenem-resistant Pseudomonas aeruginosa (CRPA) are a global health concern. The antimicrobial resistance, virulence, and molecular typing of 57 CRPA isolated from 43 patients who attended a specific Tunisian hospital from September 2018 to July 2019 were analyzed. All but one were multidrug-resistant CRPA, and 77% were difficult-to-treat-resistant (DTR) isolates. The blaVIM-2 gene was detected in four strains (6.9%), and among the 36 blaGES-positive CRPA (62%), the blaGES-5 gene was the predominant variant (86%). Three strains co-harbored the blaVIM-2 and blaGES-45 genes, and seven CRPA carried the blaSHV-2a gene (14%). OprD alterations, including truncations by insertion sequences, were observed in 18 strains. Regarding the 46 class 1 integron-positive CRPA (81%), the blaGES-5 gene was located in integron In717, while the blaGES-29 and blaGES-45 genes were found in two new integrons (In2122 and In4879), and the blaVIM-2 gene was found in In1183 and the new integron In2142. Twenty-four PFGE patterns and thirteen sequence types (three new ones) were identified. The predominant serotype O:11 and exoU (81%) were mostly associated with ST235 and the new ST3385 clones. The seven blaSHV-2a-CRPA from different patients belonged to ST3385 and the same PFGE pattern. The blaGES-5- and blaVIM-2 + blaGES-45-positive CRPA recovered mostly from ICU patients belonged to the high-risk clone ST235. Our results highlight the alarming prevalence of blaGES-5- and ST235-CRPA, the co-existence of blaGES-45 and blaVIM-2, and their location within integrons favoring their dissemination.